Experimental Study on Mechanical Behaviors of Loess Based on Two Different Modes of Oil Contamination. (3rd May 2022) - Li, Rongjian; Zhang, Shibin; Li, Rongjin; Bai, Weishi; Wang, Lei
Abstract : When loess is contaminated by oil, different modes of contamination will have a certain impact on the mechanical behaviors of loess in the oil-production areas. This study is aimed at evaluating the effect of diesel oil contamination on mechanical behaviors of loess through extensive laboratory tests. Two different modes of oil contamination were proposed and applied in compression tests, direct shear tests, and unconfined compressive strength tests to study the compressibility and strength characteristics of diesel-contaminated loess. Results show that two different modes of oil contamination have significant effects on the mechanical behaviors of loess. In comparison with clean loess, the compressibility of contaminated loess increases, and its unconfined compressive strength and shear strength all decrease under the first mode of oil contamination. The compression modulus, friction angle, and unconfined compressive strength of diesel oil-contaminated loess using the second mode of oil contamination are larger than those in the first mode of oil contamination at the same oil content and dry density. Understanding these effects on mechanical behaviors of loess under different modes of oil contamination can significantly guide soil and environment-remediation activities in loess oil-production areas.